ANTI -NMDA RECEPTOR ENCEPHALITIS: A POSSIBLE APPROACH TO DEVELOP A COST-EFFECTIVE TEST FOR ANTI NMDA RECEPTOR ANTIBODY DETECTION - Sheikh, Shafain; Tahir Aziz Ahmed; Arsalan Ahmad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Autoimmune encephalitis (AIE) has been ranked as the third most common cause of encephalitis after viral encephalitis and acute disseminated encephalomyelitis. The estimated incidence is 5-8 cases per 100,000 population. The objective of this study was to develop a cost-effective test for detection of anti NMDA R antibodies by using in house prepared rodent brain tissue sections which could facilitate timely diagnosis and management of anti NMDA R Encephalitis, which if left undiagnosed may prove fatal. Methods: A total of 500 samples sent for autoimmune encephalitis related antibody testing were included in this cross-sectional study from April 2019 to March 2021 at department of Immunology, Shifa International Hospital (SIH), Islamabad. Rodent brain was dissected to prepare tissue sections on which samples were tested by Indirect Immunofluorescence. Simultaneously samples were tested on cell-based assay (CBA) which is gold standard for testing anti NMDA R antibodies. Sensitivity, specificity, positive and negative predictive values were calculated. Results: Median age of patients who tested positive for anti NMDA encephalitis was 19 years (range: 1 to 57). Out these 76% were female and 24% males. 5% patients tested positive for anti NMDA antibodies out of those suspected to be suffering from autoimmune encephalitis. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of rodent brain IF for anti-NMDR antibodies taking CBA as gold standard was 92.6%, 98.5%, 78.1% and 99.6% respectively. The accuracy of the procedure was 98.2%. Conclusion: Indirect immunofluorescence (IF) on rodent brain tissue sections can be useful as a cost-effective alternate for resource constrained laboratories for timely detection of anti NMDA R antibodies facilitating timely diagnosis and management of anti-NMDA receptor encephalitis patients.